2018
DOI: 10.1029/2018ja025523
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Intervals of Exceptionally Strong Solar Rotation Recurrence of Galactic Cosmic Rays

Abstract: Two intervals of exceptionally strong recurrence of galactic cosmic ray (GCR) intensity at solar rotation period stand out in recent history, one in 2007–2008 and the other in 2014–2015. We use neutron monitor data from Oulu and Hermanus, solar wind (SW) data, and coronal images to study these intervals. We find that in both cases the source of solar rotation period recurrence was a coronal hole (CH), but CH structures were different. While a large, longitudinally asymmetric CH existed at high southern latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…One of its extension, the cross-wavelet transform (CWT), can be applied to determine the relative phase difference between the two time series (Grinsted et al 2004). This technique has been successful used in a broad range of research aspects of solar physics fields, such as Xiang & Kong (2015), Roberts et al (2017), Xu et al (2017), Gil & Mursula (2018), Keys et al (2018), and so on.…”
Section: Phase Relationship Between Coronal Rotation and Solar Activitymentioning
confidence: 99%
“…One of its extension, the cross-wavelet transform (CWT), can be applied to determine the relative phase difference between the two time series (Grinsted et al 2004). This technique has been successful used in a broad range of research aspects of solar physics fields, such as Xiang & Kong (2015), Roberts et al (2017), Xu et al (2017), Gil & Mursula (2018), Keys et al (2018), and so on.…”
Section: Phase Relationship Between Coronal Rotation and Solar Activitymentioning
confidence: 99%
“…Solar minima are periods of low activity when modulation is weak and GCR intensities are the highest, while during solar maxima modulation is strong and GCR intensities are at their lowest levels. Gil & Mursula (2018) compared the two exceptionally strong recurrences of GCR intensities during two solar periods of 2007-2008 and 2014-2015 using neutron monitor data, solar wind data, and coronal extreme ultraviolet images. They found that in the most recent period there was a coronal hole in the southern hemisphere about 3-4 days before each decrease in the CR intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In our calculations we follow Torrence & Webster (1999) using tools given by Jevrejeva et al (2003) and Grinsted et al (2004). Comparing solar minimum 23/24 and 24/25 it is clear that in all of the studied parameters the 27-days variation was prevalent in both time intervals, although was more incessantly visible during the former one (compare, e.g., Modzelewska & Alania 2013;Gil & Mursula 2018;Jian et al 2019). The relationships in time-frequency domain around solar rotation period between GCR and other studied time series were analyzed using the cross wavelet transform (XWT).…”
Section: Periodic Gcr Variations and Heliospheric Parametersmentioning
confidence: 99%